PENGARUH NET PROFIT MARGIN, RETURN ON ASSET, RETURN ON EQUITY, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO DALAM MEMENGARUHI HARGA SAHAM (Studi Empiris pada Perusahaan yang terdaftar pada Indeks LQ45 tahun 2021-2023) - Mohamad Taufan Akbar Fahrudin; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of Net Profit Margin, Return on Asset, Return on Equity, Earning Per Share, and Debt to Equity Ratio in influencing stock prices. The population in this study are companies listed in the LQ45 sector in the 2021-2023 period. The sampling method used in this study was purposive sampling. The total number of samples in this study were 86 research samples. The data used in this study were obtained from the official website of the Indonesia Stock Exchange (IDX). The data in this study were analyzed using multiple linear regression. The data in this study were also analyzed using the classical assumption test before the data were tested using multiple regression tests. The results of this study indicate that Net Profit Margin, Return on Asset, Return on Equity have no effect on stock prices. While Debt to Equity Ratio and Earning Per Share have an influence on stock prices.